أثر سياسة تغيير قيمة العملة وشكلها في علاج الأزمة المالية: دراسة قياسية تحليلية على الاقتصاد الليبي - الجيباني، صقر حمد; اندارة، يوسف محمد محمد (المعهد العالي للعلوم والتقنية درنة, 2018)
هدفت هذه الورقة العلمية إلى إلقاء الضوء على جدوى قيام السلطة النقدية بتخفيض مفترض في قيمة العملة الوطنية لمعرفة مدى نجاعة هذه السياسة في حلحلة الأزمة المالية والاقتصادية التي تعصف بالاقتصاد الليبي وذلك بإجراء التحليل القياسي والتفسير الاقتصادي للنتائج ومناقشتها من خلال قياس وتحليل أثر تغيير سعر صرف الدينار الليبي بالنسبة للدولار الأمريكي (EXR) على بعض المتغيرات الاقتصادية الكلية للاقتصاد الوطني الوثيقة الصلة بالأزمة المالية والاقتصادية وهي قطاع التجارة الخارجية بشقيه الصادرات (EX والواردات (IM) وعرض النقود بمفهومه الضيق (MS1) ومعدل التضخم (INF)، إضافة إلى إدراج متغير وهمي (dummy variable) لكل من الصادرات والواردات لينوب عن قياس الأزمات السياسية والأمنية التي مرت بها ليبيا خلال فترة الدراسة والتي كان لها تأثير على قطاع التجارة الخارجية للاقتصاد الليبي وتضمنت فترة الحصار الاقتصادي الذي فرض على ليبيا من قبل الولايات المتحدة والأمم المتحدة خلال عقد التسعينيات وأحداث الثورة الليبية 2011 و تطور الأوضاع الأمنية والسياسية من عام 2013 إلى 2016. واستخدم الباحثان البرنامج الإحصائي المتخصص في الاقتصاد القياسي EViews9 وتم تحليل بيانات السلاسل الزمنية للدراسة بنموذج متجه الانحدار الذاتي (VAR) لتحليل اتجاه السببية لجرانجر Granger Causality ومعرفة ردات الفعل الفورية Impulse Responses وتجزئة التباين Variance Decompositions في حال حدوث دفعة أو صدمة أو تغيير في النموذج القياسي للدراسة. كما هدفت الورقة إلى تقديم مقترح لحل أزمة السيولة في ليبيا بإتباع سياسة تغيير شكل العملة المحلية وذلك بسحب العملة الورقية في التداول واستبدالها بعملة جديدة توزع على المواطنين بمراحل كبديل لسياسة تخفيض قيمة العملة من خلال إبراز أهم الإيجابيات المتوقع تحقيقها جراء تطبيق مثل هذه السياسة وعرض سلبياتها وتحدياتها وأثرها في علاج أزمة السيولة النقدية بالاقتصاد الوطني.
The aim of this paper is to shed light on the feasibility of the monetary authority to reduce the assumed value of the national currency to determine the effectiveness of this policy in solving the financial and economic crisis affecting the Libyan economy by conducting a standard analysis and economic interpretation of the results and discuss it by measuring and analyzing the impact of changing the exchange rate of the Libyan dinar to the US dollar (EXR) based on some of the macroeconomic variables of the national economy which are closely linked to the financial and economic crisis, which are the foreign trade sector in both exports (EX), imports (IM), money supply (MS1) and inflation rate (INF), in addition to the inclusion of a dummy variable for both exports and imports, in order to measure the political and security crises experienced by Libya during the study period, which resulted to have an impact on the foreign trade sector of the Libyan economy, including the period of the economic siege imposed on Libya by the United States and the United Nations during the nineties, the events of the Libyan revolution on 2011 and the ongoing security and political situation from 2013 to 2016. The researchers used EViews, a statistical program specialized in econometrics and used the Time Series Analysis of the VAR model to analyze Granger Causality's to detect the Impulse Responses and Variance Decompositions in case of impulse or change in the standard model of the study. The paper also aimed at presenting a proposal to solve the liquidity crisis in Libya by following the policy of changing look the local currency by withdrawing the paper currency in circulation and replacing it with a new currency distributed to the citizens in stages as an alternative to the devaluation policy by highlighting the most important positive expected to be achieved by the implementation of such a policy and the presentation of the disadvantages and challenges and their impact in addressing the crisis of liquidity in the national economy
Keywords: السياسة النقدية -- الأزمات المالية -- الاقتصاد القياسي -- ليبيا